2018
DOI: 10.1002/gj.3080
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis and tectonic implication of the Late Mesozoic volcanic rocks in East Mongolia

Abstract: This paper presents new geochemical and geochronological data of the Late Mesozoic volcanic rocks in East Mongolia. These volcanic rocks belong to high‐K calc‐alkaline and shoshonitic series and exhibit features of bimodal rocks. The mafic rocks have elevated incompatible trace element concentrations and significantly negative Nb, Ta, and Ti anomalies, with 87Sr/86Sr(i) and ƐNd(t) values of 0.70502–0.70572 and −1.72459 to +1.720736, respectively, which suggest that the mafic magma was derived from a lithospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 106 publications
(174 reference statements)
1
5
0
1
Order By: Relevance
“…The εHf (t) results from the discordantly overlying, post-collisional continental red beds document that moderate juvenile and juvenile volcano-plutonic sources continued activity during Mesozoic until Early Cretaceous [70,71]. The~160-120 Ma detrital zircon age data we obtained match the regionally occurring surficial volcanic activity, which was sourced in a metasomatized depleted lithospheric mantle with minor crustal contamination [70,71].…”
Section: Gurvansayhan Terranesupporting
confidence: 56%
“…The εHf (t) results from the discordantly overlying, post-collisional continental red beds document that moderate juvenile and juvenile volcano-plutonic sources continued activity during Mesozoic until Early Cretaceous [70,71]. The~160-120 Ma detrital zircon age data we obtained match the regionally occurring surficial volcanic activity, which was sourced in a metasomatized depleted lithospheric mantle with minor crustal contamination [70,71].…”
Section: Gurvansayhan Terranesupporting
confidence: 56%
“…Mesozoic volcanic rocks in East Mongolia erupted during late Jurassic-Early Cretaceous (ages ranging from ca. 155 to 99 Ma), essentially coeval with those of the adjacent Great Xing'an Range of NE China continent (e.g., Pei et al, 2008;Dash et al, 2013;Bars et al, 2018), whereas other basalts were formed in South Mongolia during 114 to 90 Ma. In contrast to the Mesozoic basalts of East Mongolian, the late Cretaceous volcanism in south Mongolia relatively are scattered over large area, where the early Cenozoic volcanic complex of 60-50 Ma were also distributed (Enkhtuvshin et al, 1995;Barry et al, 2003;Yarmolyuk et al, 2015).…”
Section: Geological Backgroundmentioning
confidence: 98%
“…Mongolia, demonstrated that bimodal series arc type volcanic rocks migrates from west to east with time. Their origin was linked to the backarc extension induced by slab rollback of the westward-subducted Pacific Plate (Dash et al, 2013;Bars et al, 2018). In contrast, South Mongolian volcanic rocks are isolated in space and have relatively smaller outcrop which is erupted both late Cretaceous and Early Cenozoic.…”
Section: Mongolian Geoscientistmentioning
confidence: 99%
See 1 more Smart Citation
“…В полном объёме такая история прослеживается для Гоби-Алтайской и Западно-Забайкальской областей [2,4,5]. В отличие от них, развитие Восточно-Монгольской области не прослеживалось за границы раннего мела [6,7], что ставило под сомнение применимость к ней представлений о её принадлежности к вулканической провинции. В сообщении приводятся геохимические и геохронологические данные, которые свидетельствуют, во-первых, о продолжении магматической активности в пределах Восточно-Монгольской области в позднем мелу и кайнозое и, во-вторых, о соответствии тенденций в изменении состава её магматических продуктов тем же закономерностям, которые были установлены для других вулканических областей.…”
unclassified